Indian armed forces in 2047: at the centenary of independence - Banerjee, Gen Gautam (ed.) (New Delhi Vivekananda, 2023)
The 75th Year of Independence is a milestone in India$1 (Bs march towards a sovereign dispensation characterised by freedom, peace, and prosperity.s
Keywords: Indian armed forces